THREE METHODS TO EVALUATE THE USE OF EVAPORATIVE COOLING FOR HUMAN THERMAL COMFORT - Camargo, J. R.; Ebinuma, C. D.; Cardoso, S. (Revista de Engenharia Térmica, 2006)
This paper presents three methods that can be used as reference for efficient use of evaporative cooling systems, applying it, latter, to several Brazilian cities, characterized by different climates. Initially it presents the basic principles of direct and indirect evaporative cooling and defines the effectiveness of the systems. Afterwards, it presents three methods that allows to determinate where the systems are more efficient. It concludes that evaporative cooling systems have a very large potential to propitiate thermal comfort and can still be used as an alternative to conventional systems in regions where the design wet bulb temperature is under 24ºC.